2009
DOI: 10.1111/j.1540-6237.2009.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Public Responses to Health Disparities: How Group Cues Influence Support for Government Intervention*

Abstract: To examine whether public support for government intervention to address health disparities varies when disparities are framed in terms of different social groups. Copyright (c) 2009 by the Southwestern Social Science Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 23 publications
3
40
2
Order By: Relevance
“…First, although we selected messages used in public debate to date, the short messages do not reflect the full range of claims about health disparities in public discourse, particularly because we included messages only about socioeconomic-based health disparities. An alternative specified group would likely produce different responses, given that research has found greater willingness to take action to remedy disparities when low socioeconomic status groups are the identified disadvantaged group compared with racial groups (Rigby, Soss, Booske, Rohan, & Robert, 2009). Second, the messages deliberately did not feature a specific source, but the source would likely have an important role in muting (or even exacerbating) reactance.…”
Section: Limitationsmentioning
confidence: 97%
“…First, although we selected messages used in public debate to date, the short messages do not reflect the full range of claims about health disparities in public discourse, particularly because we included messages only about socioeconomic-based health disparities. An alternative specified group would likely produce different responses, given that research has found greater willingness to take action to remedy disparities when low socioeconomic status groups are the identified disadvantaged group compared with racial groups (Rigby, Soss, Booske, Rohan, & Robert, 2009). Second, the messages deliberately did not feature a specific source, but the source would likely have an important role in muting (or even exacerbating) reactance.…”
Section: Limitationsmentioning
confidence: 97%
“…We also find in this article that evaluations of the fairness of health disparities depend on the social group that is depicted as disadvantaged and on beliefs about the causes of disparities (which also vary consistently depending on the social group depicted). Other research has shown that the social group affected by an inequality influences not only the public's beliefs about the causes of that inequality but also the preferred policy response (Rigby et al 2009;Gollust and Lynch 2010).…”
Section: Implications For Politicsmentioning
confidence: 99%
“…We encourage public and private entities to 1) review what many states achieved in both general improvement and disparity reduction and 2) set policy and investment priorities in accordance with their own values and perspectives (23). …”
Section: Discussionmentioning
confidence: 99%